Current and emerging technologies for carbon accounting in urban landscapes: Advantages and limitations - Salma Habib (10971426) (2023)
Carbon capture, storage, and sequestration are crucial for mitigating climate change's adverse effects. To limit global temperature rise within the 2 °C target, it is essential to implement both artificial and natural carbon-capturing techniques and utilize renewable resources. Natural carbon sinks serve as vital resources for CO2 reduction, but quantifying their carbon sequestration is complex due to potential CO2 release from the upper ocean. Accurate assessment requires detailed modeling of interacting natural processes. This review critically examines various natural carbon pools, methodologies, and modeling techniques for carbon accounting, particularly in urban landscapes. The strengths and limitations of each approach are analyzed, leading to specific recommendations. Socio-economic benefits associated with natural carbon sinks are also presented. Ground and field measurements are found to be the most accurate methods, while accounting methods tend to be study-specific. Additionally, satellite earth observation, drone, and airborne measurements have significant potential for enhancing ecosystem analysis, assessment, and mapping. By comprehensively assessing these factors, this review contributes to the development of effective strategies for carbon accounting and management in diverse environments. Other Information Published in: Ecological Indicators License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecolind.2023.110603